SEISMIC VULNERABILITY MICROZONATION USING HORIZONTAL TO VERTICAL SPECTRAL RATIO (HVSR) METHOD IN GARUNGLOR VILLAGE AND ITS SURROUNDINGS WONOSOBO REGENCY - Cindiwati, Cindiwati; Putra, Ngurah Made Darma; Adhi, M. Aryono; Wibowo, Nugroho Budi; Ardiyansyah, Adam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research makes a significant contribution to geotechnics and seismology by providing a database of dominant frequencies and amplifications in Indonesia. The results can be used for spatial planning, earthquake risk mitigation, and understanding variations in soil characteristics and potential seismic amplification across regions to support safer development. Garunglor Village and its surroundings in Sukoharjo District, Wonosobo Regency, have a thick sedimentary layer dominated by alluvial rocks, topsoil, and mud, with low dominant frequencies. At several rock formation measurement points (Tomt, QTlb, and Tptl), the dominant frequency values varied, indicating diverse sediment characteristics. Low seismic wave amplification was found at 5 research points. The seismic vulnerability index was also low at the 8 research points, with T12 having the lowest value, making it the most suitable area for relocation. These results indicate that areas with low amplification and vulnerability indexes in Garunglor Village and its surroundings are relatively safe from potential earthquakes.